A New Schumpeterian Growth Theory (NSGT): the way out of Europe's middle-technology trap - Peter Bofinger (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2025)
As the Draghi report shows, Europe needs to undergo a fundamental transformation in order to escape its 'mid-technology trap'. Mainstream economic theory offers little guidance on how to achieve this. A critical review of neoclassical growth theory shows that in these models, growth and innovation are gradual, risk-free processes driven by individual agents, providing no rationale for the active involvement of entrepreneurs, bankers, or the government. Consequently, traditional supply-side policies advocate a strategy in which the government is perceived as the problem rather than the solution. This paper presents a New Schumpeterian Growth Theory (NSGT) based on Josef Schumpeter's key insights. Key elements of the NSGT include the crucial importance of the financial sector as a financier of growth, the element of risk and uncertainty in the innovation process, the disruptive nature of innovation and growth, and the impact of growth on inflation. While Schumpeter ascribed a key role to 'the banker' in selecting promising innovation projects, the experience of many Asian countries shows that the state can also fulfil this function successfully. For Europe, this implies that the way out of the mid-technology trap is not to reduce the role of the state, but rather to increase it through a comprehensive industrial policy strategy.
Keywords: O11; O16; O25; O42; 330; Innovation; Growth theory; Industrial policy; Schumpeter; Finance and growth